The German aesthetic tradition - Hammermeister, Kai (Cambridge University Press, 2002)
This is the only available systematic overview of German aesthetics from 1750 to the present. It begins with the work of Baumgarten and covers all the major writers on German aesthetics that follow. It offers a clear, non-technical exposition of ideas, placing these in a wider philosophical context where necessary.